Theory and Methods in Political Science (Palgrave Macmillan, 2002)
The new edition of this widely-used text introduces students in an accessible way to the approaches and methods of political science. The book has been systematically revised throughout with most chapters entirely new to this edition. The second edition features substantial extra coverage of methodological issues, an additional chapter on the philosophical underpinnings of the study of politics and a simplified structure for the presentation of theories and approaches